Exploring the effectiveness of developing preservice teachers’ knowledge of primary mathematics curriculum through professional placement experiences - Xiaowen Ma; Robin Averill; Linda Bonne (Cogent Education)
Knowledge of curriculum (KOC) is an important aspect of pedagogical content knowledge (PCK) for mathematics teaching that helps ensure effective teaching and benefits learning. Professional placement experiences, or practicum, provides preservice teachers (PTs) with classroom-based activities and in China is the final chance to enhance PCK before entering the teaching profession. This reseach aims to study the effectiveness of practicum for developing PTs’ four subcomponents of KOC for teaching primary proportions (decimals and fractions) during a 2-month practicum in China. Data was collected using the Content Representation questionnaires and follow-up interviews at the beginning and end of practicum, was analysed deductively, and levels of each component determined based on a rubric. Findings indicated that practicum was effective for improving some aspects of KOC. However, PTs’ final scores had not yet reached the maximum level, according to the rubric, and some components were the same as their initial score or dropped to the lowest level. The PTs appeared to rely heavily on textbooks. Implications included that the development of KOC in practicum alone was insufficient and further methods for developing some KOC components within initial teacher education or early in teaching careers were needed.